2023
DOI: 10.1007/s12012-022-09775-1
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Lasia spinosa (Linn.) Dissipates Chemical-Induced Cardiotoxicity in an Animal Model

Abstract: Lasia spinosa (L.) Thwaites is a medicinal plant of enormous traditional use with insu cient scienti c evidence. This research screened the antioxidative effect of L. spinosa extracts by measuring the total phenolic content, total avonoid content, DPPH free radical scavenging activity, ABTS scavenging activity, Iron chelating activity, and Ferric reducing power followed by an evaluation of in-vivo cardioprotective effect in doxorubicin-induced Wistar albino rats. Phytochemical characterization was made by Gas-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The stems and leaves of L. spinosa possessed significant antioxidant potentials and used as prospective functional foods [ 30 ]. It has been demonstrated that L. spinosa exhibits cardioprotective properties against doxorubicin-induced cardiotoxicity by normalizing specific biochemical markers, notably creatinine kinase, lactate dehydrogenase, and troponin I [ 31 ]. Although the herb has many therapeutic benefits for physical ailments, its therapeutic impact on neurological disorders has yet to be empirically assessed.…”
Section: Introductionmentioning
confidence: 99%
“…The stems and leaves of L. spinosa possessed significant antioxidant potentials and used as prospective functional foods [ 30 ]. It has been demonstrated that L. spinosa exhibits cardioprotective properties against doxorubicin-induced cardiotoxicity by normalizing specific biochemical markers, notably creatinine kinase, lactate dehydrogenase, and troponin I [ 31 ]. Although the herb has many therapeutic benefits for physical ailments, its therapeutic impact on neurological disorders has yet to be empirically assessed.…”
Section: Introductionmentioning
confidence: 99%